2021
DOI: 10.3390/microorganisms9050998
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of Anguillid Herpesvirus 1 Strains Reveal Evolutionary Disparities and Low Genetic Diversity in the Genus Cyprinivirus

Abstract: Anguillid herpesvirus 1 (AngHV-1) is a pathogen of eels and a member of the genus Cyprinivirus in the family Alloherpesviridae. We have compared the biological and genomic features of different AngHV-1 strains, focusing on their growth kinetics in vitro and genetic content, diversity, and recombination. Comparisons based on three core genes conserved among alloherpesviruses revealed that AngHV-1 exhibits a slower rate of change and less positive selection than other cypriniviruses. We propose that this may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 117 publications
1
13
0
Order By: Relevance
“…Our recent evidence supporting a general low degree of diversity among cyprinivirus species clades compared to species clades within the family Herpesviridae suggests that a high degree of purifying selection has occurred after species clade divergence (Donohoe et al, 2021). We speculated that this difference could be linked, at least in part, to fundamental differences in biology between members of the two distantly related virus families.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our recent evidence supporting a general low degree of diversity among cyprinivirus species clades compared to species clades within the family Herpesviridae suggests that a high degree of purifying selection has occurred after species clade divergence (Donohoe et al, 2021). We speculated that this difference could be linked, at least in part, to fundamental differences in biology between members of the two distantly related virus families.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to the family Herpesviridae there are relatively few studies regarding evolution within the family Alloherpesviridae (Aoki et al, 2007;Davison et al, 2013;Waltzek et al, 2009Waltzek et al, , 2005. Recently, we investigated the diversity of core gene sequences within species clades of the genus Cyprinivirus (referred to as cypriniviruses and comprising alloherpesviruses infecting cyprinids and eels) (Donohoe et al, 2021). This revealed significantly less genetic diversity within cyprinivirus species clades than within species in the family Herpesviridae, which may be linked, at least in part, to different environmental pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The AngHV-1 Luc-copGFP and the CyHV-2 Luc-copGFP recombinant strains both encode the same reporter genes consisting of the Luc2 cassette and a copepod ( Pontellina plumata ) GFP (copGFP) cassette linked by a T2A sequence, driven by a eukaryotic translation elongation factor 1 alpha (EF-1α) promoter. To generate these recombinants, the dual Luc2/copGFP cassette was inserted in the region between ORF32 and ORF33 in the AngHV-1 UK parental strain genome (GenBank accession MW580855.1) [ 40 ] (Delrez et al, unpublished data) and in the intergenic region between ORF64 and ORF66 in CyHV-2 YC-01 parental strain genome (GenBank accession no. MN593216.1) (He et al, unpublished data) using homologous recombination in eucaryotic cells, as described previously [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to CyHV-3, the genus Cyprinivirus contains two other economically important viruses: anguillid herpesvirus 1 (AngHV-1) and cyprinid herpesvirus 2 (CyHV-2) [ 40 ]. AngHV-1 infects the European eel ( Anguilla anguilla ), Japanese eel ( Anguilla japonica ), and American eel ( Anguilla rostrata ) [ 41 ]; CyHV-2 also infects goldfish ( Carassius auratus ) and the closely related Prussian carp ( Carassius gibelio ) and crucian carp ( Carassius carassius ) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high-energy requirement for spawning migration and the dysfunction of the swim bladder have an adverse effect on individuals with reduced lipid stores due to infection (Marohn et al, 2013). The AngHV-1 infection causes the following symptoms: lethargy; swimming near the surface; swimming in a circular motion; mottled skin; inflammation; haemorrhaging in the fins; throat, operculum, head, lower jaw, pectoral fin, tail and skin lesions; and necrosis within the kidney, gills and liver (Haenen et al, 2012;Armitage et al, 2014;McConville et al, 2018;Donohoe et al, 2021). Armitage et al (2014) reported dead eels measuring 50-90 cm (17-26 years old) due to AngHV-1 infection in two English still-water fisheries, but experimental infections did not produce eel mortality (see also Kobayashi and Miyazaki, 1996;Hangalapura et al, 2007).…”
mentioning
confidence: 99%